Grain price and volatility transmission from international to domestic markets in developing countries - Ceballos, Francisco; Hernandez, Manuel A.; Minot, Nicholas; Robles, Miguel (Agricultural and Applied Economics Association, 2015)
Understanding the sources of domestic food price volatility in developing countries and the extent to which it is transmitted from international to domestic markets is critical to help design better global, regional, and domestic policies to cope with excessive food price volatility and to protect the most vulnerable groups. This paper examines price and volatility transmission from major grain commodities to 41 domestic food products across 27 countries in Africa, Latin America, and South Asia. We follow a multivariate GARCH approach to model the dynamics of monthly price volatility in international and domestic markets. The period of analysis is 2000 through 2013. In terms of price transmission in levels, we only observe lead-lag relationships from international to domestic markets in few cases. To calculate volatility spillovers, we simulate a shock equivalent to a 1% increase in the conditional volatility of prices in the international market and evaluate its effect on the conditional volatility of prices in the domestic market. The transmission of price volatility is statistically significant in just one-quarter of the maize markets tested, almost half of rice markets tested, and all wheat markets tested. Volatility transmission seems to be more common when trade (imports or exports) are large relatively to domestic requirements.